Commodification of Identity in Local Political Contests on Instagram: Komodifikasi Identitas Pada Kontestasi Politik Lokal di Instagram - Amalia, Fara Putri; Dharma, Ferry Adhi (Kanal: Jurnal Ilmu Komunikasi, 2025)
Identity politics, such as ethnicity, religion, and local traditions, are often exploited to win political competition. Social media platforms like Instagram have become strategic media for building image and mobilizing support through visual content. This study examines the construction of political hyperreality by two official mayoral candidate accounts, namely @achmadamiraslichin and @cakband1, on the Instagram platform using Baudrillard's Simulacra and Simulation theory approach. By packaging visual posts, this couple creates a "hyperreality" that reinforces the narrative that they are the ideal choice for the people of Sidoarjo. This research aims to analyze the commodification of cultural Islamic identity in the local political contestation in Sidoarjo through the digital space, namely the Instagram platform during the Sidoarjo 2024 regional election. This research is a type of qualitative study using analysis through the theoretical perspective of Baudrillard. The Instagram platform, dominated by users of productive age (25–34 years), has become an arena for political simulation where visual images are more influential than actual programs. The implication is that identity politics on social media not only commodifies religion but also has the potential to trigger polarization, especially among young voters with limited digital literacy. This study shows that the 2024 Sidoarjo regional election is undergoing a digital transformation, where both candidates are utilizing cultural Islamic identity to build a religious image and closeness with voters, particularly Nahdliyyin residents.